Voltage-composition profile and synchrotron X-ray structural analysis of low and high temperature LixCoO2 host material - Bueno, Paulo Roberto [UNESP]; Pesquero, Naira Canevarolo [UNESP]; Ferreira, Fabio Furlan; Santiago, Elisabete Inacio; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (Amer Chemical Soc, 2008)
In the present work, the intercalation of lithium ions in the LixCoO2 host material was investigated by means of the discharge curves and voltage-composition profile with the main goal of establishing a close correlation between the voltage-composition patterns and the structure of the LixCoO2 prepared at low and high temperatures. As a result, the structures of the LixCoO2 prepared at low and high temperatures were investigated by a careful analysis of synchrotron X-ray powder diffraction (including a quantitative Rietveld refinement), which showed the presence of two majority phases for LixCoO2 prepared at low temperature, that is, spinel and layered phases. on the basis of the information provided by the quantitative structural analysis, the voltage-composition profiles were interpreted by considering at least two ionic modes of charges, one in which lithium ions occupy sites in the spinel structure and the other in which lithium ions occupy the sites of the layered structure. It was found that at least two modes (two types of site to charged) of charge were related to the layered structure during ionic charging of the host. Finally, and curiously, it was found that the decreasing of the charge capacity as a function of charge-discharge cycles is mainly related to a type of site located in the layered structure (or sites related to layered phase transition, i.e. order-disorder transition from hexagonal to monoclinic symmetry).